2015
DOI: 10.1002/icd.1911
|View full text |Cite
|
Sign up to set email alerts
|

Parents Support Preschoolers' Use of a Novel Interactive Device

Abstract: Past research has found that preschool children's ability to learn educational content from interactive media may be hindered by needing to learn how to use a new interactive device. However, little research has examined the instructional supports parents provide while their children use interactive media. Forty-six preschool children and their parents participated in a 30-min interaction with a novel interactive device. Children were assessed before and after the interaction on knowledge of letters and number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
2
15
0
Order By: Relevance
“…In the present study, parents reduced their spatial language input in the 2D iPad ® play context as their children increased in age. Similar observations have also been reported by Flynn and Richert () examining parental verbal input of 3‐ and 4‐year‐olds' use of novel computer‐based games focusing on alphabets and numbers. Older preschoolers also received fewer parental content‐related input compared to their younger peers.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, parents reduced their spatial language input in the 2D iPad ® play context as their children increased in age. Similar observations have also been reported by Flynn and Richert () examining parental verbal input of 3‐ and 4‐year‐olds' use of novel computer‐based games focusing on alphabets and numbers. Older preschoolers also received fewer parental content‐related input compared to their younger peers.…”
Section: Discussionsupporting
confidence: 84%
“…No significant relationships were found between touchscreen use and either gross motor or language milestones. These data provide converging evidence with other work suggesting the potential power of digital tools to facilitate learning such as letter and number recognition (Flynn and Richert, 2015) and knowledge transfer from media learning to analogous physical problems (Huber et al, 2016; see also Semmelmann et al, 2016). …”
Section: Discussionsupporting
confidence: 79%
“…It also appears that there are strategies that parents can use to enhance children’s learning when using interactive media. Research by Flynn and Richert (2015) showed that using novel interactive media allowed children to perform better on letter and number recognition and device knowledge when parents focused on the content of what was being learned, rather than focusing on the device itself. Therefore, when evaluating the efficacy of any learning approach it is important to consider the broader social context, including the level of parental and teacher involvement as well as the parents’ and teacher’s beliefs about its efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Also, parent-child co-play varies widely between families (just like co-viewing of television programming), and this variation intersects in predictable ways with broader patterns of parent-child closeness, communication, and parental involvement in child learning (Wang, Taylor, & Sun, 2018). Notably, many parents are unsure of best practice to support their children's learning during co-play interactions, which could be remedied via research-based guidelines on how to do so (Flynn & Richert, 2015;Ho, Lee, Wood, Kassies, & Heinbuck, 2018).…”
Section: Level 1: the Impact Of Media On Cognitive Developmentmentioning
confidence: 99%